Islamophobia and Classical Orientalism: An Analysis - Abdul Rahim, Rahimin Affandi; Ramli, Mohd Anuar; Kahal, Siti Maimunah; Salleh, Muhammad Yusri bin Yusof @ Salleh; Abd Razak, Muhd Imran; Hassan, Paiz; Zainal Abidin, Mohd Zahirwan Halim (Idealogy Journal, 2018)
Following the events of September 11, 2001, there have been several attempts worldwide to disparage Islam. It is referred to as Islamophobia, and it occurs when Muslims worldwide become targets of hatred and violence. To that aim, one of this study's objectives is to reconstruct the question of whether Islamophobia was precipitated by the events of September 11, 2001, or whether it existed before to that date. The primary focus will be on Malaya's history. The methodology of this study is based on a review of western oriental writing works, which were studied within the framework of archipelago thinking. This study concludes that Islamophobia occurs as a result of two factors: first, the actions of extremists that cause unrest in the west, beginning with the events of September 11, 2001, and second, historical and contemporary western colonial orientalist writings contribute significantly to global Islamophobia.